Caracterização estrutural do nitreto de ferro silício e avaliação de sua aplicação como matéria-prima para massa de tamponamento - Savia Cristina Lacerda Poubel Bastos (2007)
The iron silicon nitride is a kind of composite obtained through nitretation of the iron silicon, the temperature and controlled pressure. Still little studied this material have some applications, where in this work is stressed the use of this as one of the raw materials in the taphole mud to blast furnace. We carried out a study about physical, chemical and microstructural characterizations of the iron silicon nitride and, evaluation of its influence when added to the taphole mud. The iron silicon nitride samples studied presented significant difference during morphology and particles size characterization. In the others properties (chemical elements presents, crystallographic phases, microstructure andgranulometric distribution of particles, well as size and volume of pores and superficial area) it was not observed significant difference. For the influence evaluation of the iron silicon nitride, the taphole muds were heat treated at 1000ºC, 1200ºC and 1400ºC. In the phases identification, the iron silicon nitride decreased during the temperature increased, due to the raw material reactions, producing Fe3Si and liberating gases constantly, N2 and CO. In the microstructural evaluation was observed the reactions in each temperature. The material porosity can be related to pores due to the constantly liberation of volatile. The material with larger nitride addition presented better compression strength. The room temperature flexural strength didnt show significant difference among taphole muds.